Poisoning the land - Weitz, Martin (New York : Gloucester Press, 1992)
Describes the ways in which we are polluting the earth and why this poses problems for us and future generations. Also examines practical solutions to prevent further pollution.
Includes index.
Keywords: Pollution -- Environmental aspects -- Juvenile literature; Environmental protection -- Juvenile literature; Pollution -- Environmental aspects; Environmental protection